Fabrication, characterization and adsorption properties of cucurbit[7]uril-functionalized polycaprolactone electrospun nanofibrous membranes - Chen, Changzhong; Liu, Fengbo; Zhang, Xiongzhi; Zhao, Zhiyong; Liu, Simin (Beilstein Journal of Organic Chemistry, 2019)
The fabrication of electrospun nanofibers comprising cucurbit[7]uril (CB[7]) and poly(ε-caprolactone) (PCL) is reported. Various techniques such as SEM, FTIR, XRD, DSC and TG were utilized to characterize the morphology, composition and properties of the nanofibers. Uniform bead-free electrospun nanofibers were obtained from PCL/CB[7] mixed solutions and the average fiber diameter of the nanofibers increases with the increase of CB[7] content. The nanofibers are composed of a physical mixture of PCL and CB[7], and CB[7] itself is present in the PCL fiber matrix in an uncomplexed state. The static adsorption behavior of the PCL/CB[7] nanofibers towards methylene blue (MB) was also preliminary investigated. The results indicate that the adsorption of MB onto the nanofibrous membranes fits the second-order kinetic model and Langmuir isotherm model.
Keywords: adsorption; cucurbit[7]uril; electrospinning; macrocycles; methylene blue; nanofiber

(untitled) - Huang, Z.-M.; Zhang, Y.-Z.; Kotaki, M.; Ramakrishna, S. (Compos. Sci. Technol., 2003)

(untitled) - Li, D.; Xia, Y. (Adv. Mater., 2004)

(untitled) - Greiner, A.; Wendorff, J. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Cashion, M. P.; Li, X.; Geng, Y.; Hunley, M. T.; Long, T. E. (Langmuir, 2010)

(untitled) - Celebioglu, A.; Uyar, T. (Chem. Commun., 2010)

(untitled) - Allison, S.; Ahumada, M.; Andronic, C.; McNeill, B.; Variola, F.; Griffith, M.; Ruel, M.; Hamel, V.; Liang, W.; Suuronen, E. J.; Alarcon, E. I. (J. Mater. Chem. B, 2017)

(untitled) - Jung, J.-W.; Lee, C.-L.; Yu, S.; Kim, I.-D. (J. Mater. Chem. A, 2016)

(untitled) - Zhang, M.; Zhao, X.; Zhang, G.; Wei, G.; Su, Z. (J. Mater. Chem. B, 2017)

(untitled) - Yang, W.; Liu, X.; Chen, L.; Liang, L.; Jia, J. (Chem. Commun., 2017)

(untitled) - Luo, J.; Luo, X.; Hu, C.; Crittenden, J. C.; Qu, J. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Uyar, T.; Kingshott, P.; Besenbacher, F. (Angew. Chem., Int. Ed., 2008)

(untitled) - Narayanan, G.; Aguda, R.; Hartman, M.; Chung, C.-C.; Boy, R.; Gupta, B. S.; Tonelli, A. E. (Biomacromolecules, 2016)

(untitled) - Uyar, T.; Havelund, R.; Nur, Y.; Balan, A.; Hacaloglu, J.; Toppare, L.; Besenbacher, F.; Kingshott, P. (J. Membr. Sci., 2010)

(untitled) - Uyar, T.; Havelund, R.; Hacaloglu, J.; Besenbacher, F.; Kingshott, P. (ACS Nano, 2010)

(untitled) - Narayanan, G.; Gupta, B. S.; Tonelli, A. E. (Biomacromolecules, 2014)

(untitled) - Aytac, Z.; Uyar, T. (Eur. Polym. J., 2016)

(untitled) - Narayanan, G.; Gupta, B. S.; Tonelli, A. E. (Polymer, 2015)

(untitled) - Celebioglu, A.; Uyar, T. (Nanoscale, 2012)

(untitled) - Aytac, Z.; Yildiz, Z. I.; Kayaci-Senirmak, F.; San Keskin, N. O.; Kusku, S. I.; Durgun, E.; Tekinay, T.; Uyar, T. (J. Agric. Food Chem., 2016)

(untitled) - Chen, M.; Wang, C.; Fang, W.; Wang, J.; Zhang, W.; Jin, G.; Diao, G. (Langmuir, 2013)

(untitled) - Wang, K.; Wang, C.-Y.; Wang, Y.; Li, H.; Bao, C.-Y.; Liu, J.-Y.; Zhang, S. X.-A.; Yang, Y.-W. (Chem. Commun., 2013)

(untitled) - Freeman, W. A.; Mock, W. L.; Shih, N. Y. (J. Am. Chem. Soc., 1981)

(untitled) - Kim, J.; Jung, I.-S.; Kim, S.-Y.; Lee, E.; Kang, J.-K.; Sakamoto, S.; Yamaguchi, K.; Kim, K. (J. Am. Chem. Soc., 2000)

(untitled) - Day, A.; Arnold, A. P.; Blanch, R. J.; Snushall, B. (J. Org. Chem., 2001)

(untitled) - Barrow, S. J.; Kasera, S.; Rowland, M. J.; del Barrio, J.; Scherman, O. A. (Chem. Rev., 2015)

(untitled) - Yang, X.; Liu, F.; Zhao, Z.; Liang, F.; Zhang, H.; Liu, S. (Chin. Chem. Lett., 2018)

(untitled) - Lagona, J.; Mukhopadhyay, P.; Chakrabarti, S.; Isaacs, L. (Angew. Chem., Int. Ed., 2005)

(untitled) - Masson, E.; Ling, X.; Joseph, R.; Kyeremeh-Mensah, L.; Lu, X. (RSC Adv., 2012)

(untitled) - Shetty, D.; Khedkar, J. K.; Park, K. M.; Kim, K. (Chem. Soc. Rev., 2015)

(untitled) - Gürbüz, S.; Idris, M.; Tuncel, D. (Org. Biomol. Chem., 2015)

(untitled) - Assaf, K. I.; Nau, W. M. (Chem. Soc. Rev., 2015)

(untitled) - Gao, R. H.; Chen, L. X.; Chen, K.; Tao, Z.; Xiao, X. (Coord. Chem. Rev., 2017)

(untitled) - Montes-Navajas, P.; Corma, A.; Garcia, H. (ChemPhysChem, 2008)

(untitled) - Chen, R.-h.; Qiao, H.-t.; Liu, Y.; Dong, Y.-h.; Wang, P.; Zhang, Z.; Jin, T. (Environ. Prog. Sustainable Energy, 2015)

(untitled) - Karcher, S.; Kornmüller, A.; Jekel, M. (Water Sci. Technol., 1999)

(untitled) - Karcher, S.; Kornmüller, A.; Jekel, M. (Water Res., 2001)

(untitled) - Zhao, R.; Wang, Y.; Li, X.; Sun, B.; Jiang, Z.; Wang, C. (Colloids Surf., B, 2015)